Secular Belief, Religious Belonging in China - Madsen, Richard (Review of Religion and Chinese Society, 2014)
A recent Gallup poll found that almost half of China’s people are atheists. However, surveys conducted by Fenggang Yang and others show that as much as 85 percent of the population periodically engages in religious practices. How can we reconcile reports of widespread atheism with those of widespread religious practice?